(untitled) (International Journal of Engineering and Computer Science, 2017)
HBase is also called the Hadoop database since it is a NoSQL database that runs on top of Hadoop. It combines the scalability of Hadoop by running on the Hadoop Distributed File System (HDFS), with real-time data right of entry as a key and value store and deep analytic capabilities of MapReduce. This article introduces HBase and describe how it organizes and manages data and then demonstrates how to set up a local HBase environment and interact with data using the HBase shell. It is a data model that is related to Google’s big table designed to provide quick random access to huge amounts of structured data. It leverages the fault-tolerance provided by the Hadoop File System (HDFS). It is a part of the Hadoop ecosystem that provides random real-time read or write access to data in the Hadoop File System. One can store the data in HDFS either directly or during HBase. Data consumer reads and accesses the data in HDFS at randomly using HBase. It stands on top of the Hadoop File System and provides read and write access. HBase is key and value store specifically it is a reliable, Distributed, Multidimensional, Sorted map. HBase stores data in the form of a cells here cells are grouped by a row key into something that looks like a row and cells are stored individually the storage is sparse. HBase Performance testing on single node cluster step-up. but here query performance is slow under single node cluster set-up so this reason you have to introduce the multi-node cluster set-up and improvement of the query performance in HBase Cluster Environment.